Early-strength clinker-free concrete prepared from ammonia alkali white mud and preparation method of early-strength clinker-free concrete

By directly using wet-based amino alkali white mud without drying to prepare clinker-free concrete, and using its chemical substances to stimulate the gelling system, the complex and pollution problems of the preparation process of ammonia alkali white mud in the prior art are solved, and efficient and low-cost preparation of early strength clinker-free concrete is achieved.

CN119591369AActive Publication Date: 2025-03-11TANGSHAN SANYOU CHEM IND +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411769159.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

In the prior art, ammonia alkali white mud needs to be dried and ground when preparing clinker-free concrete, resulting in high production costs and complex operation, and failing to effectively solve the problems of high water absorption and high alkaline pollution of ammonia alkali white mud.

Method used

Wet-based amino alkali white mud without drying is used to prepare clinker-free concrete by mechanical crushing or adding water to stir into a slurry. The chemical substances in the ammonia alkali white mud are used to stimulate the slag powder-steel slag powder-gypsum gelling system, accelerate the hydration reaction, and prepare early-strength clinker-free concrete.

Benefits of technology

The resource utilization of ammonia alkali white mud is realized, the production cost is reduced, the operation process is simplified, and the early strength of clinker-free concrete is improved, with compressive strength ≥6.0MPa in 1d, compressive strength ≥20.0MPa in 3d, and compressive strength ≥35.0MPa in 28d.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169804100000061
    Figure BDA0005169804100000061
  • Figure BDA0005169804100000071
    Figure BDA0005169804100000071
  • Figure BDA0005169804100000081
    Figure BDA0005169804100000081
Patent Text Reader

Abstract

The invention relates to early strength type clinker-free concrete prepared from ammonia alkali white mud and a preparation method thereof. The early strength type clinker-free concrete is prepared from the following components in parts by mass: 65 to 235 parts of ammonia alkali white mud, 140 to 245 parts of slag powder, 35 to 105 parts of steel slag powder, 30 to 60 parts of industrial byproduct gypsum, 770 to 895 parts of fine aggregate, 1040 to 1070 parts of coarse aggregate, 5 to 9 parts of polycarboxylate superplasticizer and 120 to 166 parts of mixing water. The clinker-free concrete does not need to be dried and can be used for preparing concrete after being crushed into fine particles or prepared into slurry, industrial products are not doped to serve as an exciting agent, the cost is reduced, and further, the 1d compressive strength of the clinker-free concrete is larger than or equal to 6.0 MPa, the 3d compressive strength of the clinker-free concrete is larger than or equal to 20.0 MPa, and the 28d compressive strength of the clinker-free concrete is larger than or equal to 35.0 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete preparation, and in particular to an early-strength clinker-free concrete prepared by utilizing ammonia-alkali white mud and a preparation method thereof. Background Art

[0002] Ammonia-soda mud (also known as "alkali slag") is a white precipitate waste discharged during the ammonia evaporation process of producing soda ash by the ammonia-soda process. Its main components are CaCO3, CaCl2, Ca(OH)2, CaSO4, etc. The production of 1 ton of soda ash will produce 0.3 to 0.6 tons of dry ammonia-soda mud. The particle size of ammonia-soda mud is generally between 2μm and 50μm. After air drying, it is easy to produce dust and then be inhaled by the human body, which is harmful to human health. Ammonia-soda mud has strong water absorption and high water content. The pH value of its leachate is about 10 to 12, which is highly alkaline. Long-term storage will cause serious pollution to the soil and groundwater. At present, the stockpile of ammonia-soda mud in my country is huge, but the comprehensive utilization rate is low. A large amount of ammonia-soda mud is stored in the open air or landfilled on the spot, which has a serious impact on the health of surrounding residents and the ecological environment.

[0003] Clinker-free concrete is a concrete made of alkali-activated cementitious materials or all-solid waste cementitious materials that do not contain cement clinker. Alkali-activated cementitious materials generally use alkali activators such as water glass and sodium hydroxide to activate granulated blast furnace slag, fly ash and other mineral powder materials with volcanic ash activity to produce cementitious properties; all-solid waste cementitious materials use steel slag, ammonia-alkali white mud, red mud, carbide slag and other materials that can hydrate and produce a large amount of OH - The industrial solid waste powder, together with the industrial by-product gypsum, stimulates the granulated blast furnace slag, fly ash, coal-fired slag and other silicon-aluminum industrial solid waste powders to produce cementitious properties. In order to meet the needs of engineering construction and the "dual carbon" goals, using industrial solid waste as the raw material of concrete and developing clinker-free low-carbon concrete is an important way for the sustainable development of the concrete industry.

[0004] Patent CN 115745434 A (Clinker-free cementitious material containing a large amount of wet alkali-discharged slag and its preparation method and application) uses NaOH and Na2CO3 composite activators to activate wet alkali-discharged slag and slag to prepare a clinker-free cementitious material. However, NaOH and Na2CO3 are industrial products with high production costs and pollutant emissions during the production process. In addition, the 3d and 28d mortar compressive strengths of the cementitious material are low, with the highest being only 12.5MPa and 34.7MPa.

[0005] In the patent CN 117049805 A (a method for preparing a cementitious material using ammonia-alkali white mud-slag-fly ash as raw materials), the ammonia-alkali white mud needs to be aired, dried and ground. Since the ammonia-alkali white mud particles are extremely fine, usually exist in the form of agglomerates and have strong water absorption, drying and grinding are difficult and costly.

[0006] Patent CN 112125633 A (C30 grade all-solid waste concrete and its preparation method) uses ammonia-alkali white mud-carbide slag to synergistically stimulate slag-fly ash instead of cement to prepare concrete. It is necessary to statically stratify the ammonia-alkali white mud and carbide slag stock solutions to obtain ammonia-alkali white mud, carbide slag upper clear liquid and lower slurry respectively, and control the moisture content of the lower slurry to 50% to 60%. Then, the lower slurry is naturally dried, crushed and sieved to obtain ammonia-alkali white mud powder and carbide slag powder respectively; when preparing concrete, it is necessary to control the concentration and pH value of the upper clear liquid of carbide slag within a certain range, and then add it to concrete for mixing. The raw material processing and concrete preparation process described in this patent are complex, inefficient, difficult to control technical indicators, and low practical feasibility. In addition, none of the above patents involve the 1d compressive strength of clinker-free cementitious materials or concrete.

[0007] Therefore, a method for preparing clinker-free concrete using ammonia-alkali white mud is needed, which does not require drying, has low production cost and is simple to operate. Summary of the invention

[0008] The invention provides an early-strength clinker-free concrete prepared by using ammonia-alkali white mud and a preparation method thereof. The ammonia-alkali white mud does not need to be dried, and no industrial product is added into the clinker-free concrete as an activator. The chemical substances contained in the ammonia-alkali white mud are utilized to activate the slag powder-steel slag powder-gypsum cementitious system, so as to accelerate the hydration reaction of the cementitious material, prepare the early-strength clinker-free concrete, and realize the resource utilization of the ammonia-alkali white mud and other solid wastes.

[0009] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0010] The invention discloses an early-strength clinker-free concrete prepared by using ammonia-alkali white mud. The components thereof include, by weight: 65-235 parts of ammonia-alkali white mud, 140-245 parts of slag powder, 35-105 parts of steel slag powder, 30-60 parts of industrial by-product gypsum, 770-895 parts of fine aggregate, 1040-1070 parts of coarse aggregate, 5-9 parts of polycarboxylic acid water reducer and 120-166 parts of mixing water.

[0011] Furthermore, the ammonia-soda mud is obtained by mechanically crushing the wet-base ammonia-soda mud after filter pressing into particles of less than 2 mm; or the wet-base ammonia-soda mud after filter pressing is mechanically crushed and stirred into slurry with water, and the water content of the slurry is controlled to be ≥140%; the slag powder is S95 grade granulated blast furnace slag powder; the steel slag powder is steel slag powder after crushing, magnetic separation and grinding, with a specific surface area of ​​≥350m 2 / kg; the coarse aggregate is pebble or crushed stone, with a particle size of 4.75-26.5mm and a crushing index of ≤20%; the fine aggregate is natural sand or machine-made sand, with a particle size of 0.15-4.75mm, a fineness modulus of 2.3-3.0, a mud content of <5.0%, or a stone powder content of <15.0%.

[0012] The present invention also provides a method for preparing early-strength clinker-free concrete by using ammonia-alkali white mud, comprising the following steps:

[0013] A. Crush the wet-base ammonia-soda white mud into particles less than 2 mm, take a sample of the ammonia-soda white mud particles and dry them at 65°C to constant weight, and respectively detect the moisture content of a% and the liquid limit moisture content of b%, and adjust with water;

[0014] B. Feed coarse aggregate, fine aggregate, ammonia-alkali white mud, slag powder, steel slag powder and industrial by-product gypsum into a concrete mixer in the following proportions by weight: 1040-1070 parts of coarse aggregate, 770-895 parts of fine aggregate, 65-235 parts of ammonia-alkali white mud, 140-245 parts of slag powder, 35-105 parts of steel slag powder and 30-60 parts of industrial by-product gypsum, and stir for 30-60 seconds;

[0015] C. Add 50% to 80% of 120 to 166 parts of mixing water into a mixer and stir for 30 to 60 seconds; add 5 to 9 parts of polycarboxylate water reducer together with the remaining mixing water into the mixer and stir for 60 to 120 seconds to obtain a concrete mixture;

[0016] D. vibrating the concrete mixture into shape, covering it with a plastic film for moisture retention and curing to obtain an early-strength clinker-free concrete.

[0017] Furthermore, the water adjustment method includes: when the water content of the ammonia-soda white mud is measured to be a% < the liquid limit water content b%, additional water needs to be added, and the amount of water added is the mass of the dry ammonia-soda white mud m·(b%-a%);

[0018] When the moisture content of the ammonia-alkali white mud is measured to be a%>b%, the actual mixing water consumption of the concrete needs to deduct part of the water consumption in the above step C, and the deducted amount of water is the mass of the dry ammonia-alkali white mud m·(a%-b%);

[0019] When ammonia-soda mud is used to prepare concrete in the form of slurry, the moisture content of the ammonia-soda mud slurry is measured to be c%. Since c% ≥ 140%, it is higher than the liquid limit moisture content b% of the ammonia-soda mud. At this time, the actual mixing water consumption of the concrete needs to deduct part of the water consumption from the water consumption in the above step C, and the deducted water amount is the dry basis ammonia-soda mud mass m·(c%-b%).

[0020] The beneficial effects of the present invention are:

[0021] The ammonia-alkali white mud in the present invention does not need to be dried, and can be used to prepare concrete after being crushed into fine particles or made into slurry; no industrial product is added as an activator, thereby further reducing the cost; the prepared clinker-free concrete has high early strength, with a 1d compressive strength of ≥6.0MPa, a 3d compressive strength of ≥20.0MPa, and a 28d compressive strength of ≥35.0MPa. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The invention provides an early-strength clinker-free concrete, comprising the following components: ammonia-alkali white mud, slag powder, steel slag powder, industrial by-product gypsum, fine aggregate, coarse aggregate, a water reducer and mixing water. The composition comprises, by mass, 65-235 parts of ammonia-alkali white mud, 140-245 parts of slag powder, 35-105 parts of steel slag powder, 30-60 parts of industrial by-product gypsum, 770-895 parts of fine aggregate, 1040-1070 parts of coarse aggregate, 5-9 parts of polycarboxylate water reducer and 120-166 parts of mixing water. The concrete has a 1d compressive strength of ≥6.0MPa, a 7d compressive strength of ≥20.0MPa and a 28d compressive strength of ≥35.0MPa.

[0024] The ammonia-soda white mud used in the present invention is obtained by mechanically crushing the wet-base ammonia-soda white mud after filter pressing into particles of less than 2 mm; or mechanically crushing the wet-base ammonia-soda white mud after filter pressing, adding water and stirring into slurry, and in order to facilitate slurry pumping, the water content of the slurry is controlled to be ≥140%;

[0025] The present invention utilizes the chemical substances contained in the ammonia-alkali white mud to stimulate the slag powder-steel slag powder-gypsum cementitious system, accelerate the hydration reaction of the cementitious material, and form a higher early strength. Generally speaking, the hydration reaction rate of the slag powder-steel slag powder-gypsum cementitious system is relatively slow, mainly because the steel slag powder needs to be hydrated to release Ca(OH)2 to form an alkaline environment in the early stage, and the glass contained in the slag powder gradually hydrates and dissociates in the alkaline environment to form silicate (aluminum) acid ions, which react with Ca(OH)2 to form hydrated calcium silicate (CSH) gel, and at the same time, calcium aluminate (AFt) is generated under the stimulation of gypsum to form early strength. However, this process is relatively slow and takes 1 to 2 days to complete at room temperature, so the cementitious system generally has no strength after 1 day. When ammonia-alkali mud is added, the alkaline substances such as Ca(OH)2 contained in the ammonia-alkali mud can quickly form an alkaline environment, accelerate the hydration and dissociation of the vitreous body in the slag powder, and form CSH gel; at the same time, a large amount of soluble chlorides and sulfates in the ammonia-alkali mud can react with the dissociated silicate (aluminum) acid ions to form complex salt precipitates such as AFt and Frieldel salt, thereby quickly forming early strength. The 1d compressive strength of the clinker-free concrete with the addition of ammonia-alkali mud is ≥6.0MPa, the 7d compressive strength is ≥20.0MPa, and the 28d compressive strength is ≥35.0MPa.

[0026] The present invention also provides a method for preparing the early-strength clinker-free concrete. In view of the characteristics of ammonia-alkali white mud that it has strong water absorption and is not easy to dry, the wet-base ammonia-alkali white mud in the present invention does not need to be dried, and is only used after being mechanically crushed or made into a slurry. When the water content of the ammonia-alkali white mud is not higher than the liquid limit water content of the ammonia-alkali white mud, the water in the ammonia-alkali white mud exists in the form of non-free water such as crystallization water or adsorbed water. Therefore, when designing the concrete mix ratio, the ammonia-alkali white mud with a water content equal to the liquid limit water content is counted as a component of the concrete cementitious material, and the water in the ammonia-alkali white mud that is higher than the liquid limit water content is counted as mixing water, and this part of water is deducted when calculating the actual water consumption. The advantage of this is that the water-cement ratio and the amount of cementitious material used in the concrete can be designed according to the parameters of ordinary concrete, and the cohesiveness of the concrete is basically the same as that of ordinary concrete. If only the dry-base ammonia-alkali mud is counted as a component of concrete cementitious materials, and the water content in the ammonia-alkali mud is counted as mixing water, then this part of non-free water will also be deducted from the mixing water amount when calculating the concrete mix ratio, resulting in a lower actual mixing water amount, and thus a lower water-cement ratio of the concrete and a higher total amount of cementitious materials, causing the concrete to be too sticky and inconvenient to construct.

[0027] Embodiment 1:

[0028] 1. Prepare early-strength clinker-free concrete with ammonia-alkali white mud, slag powder, steel slag powder, desulfurized gypsum, fine aggregate, coarse aggregate, polycarboxylic acid water reducer and water. The specific mix proportion is shown in Table 1.

[0029] Table 1 Concrete mix ratio (kg / m3 )

[0030]

[0031] 2. The water content of ammonia-soda mud is 53%, and the liquid limit water content is 105%. The ammonia-soda mud is crushed into particles less than 2 mm by a crusher;

[0032] 3. Purchased steel slag powder, with a specific surface area of ​​360m 2 / kg;

[0033] 4. Purchase S95 grade granulated blast furnace slag powder, with a specific surface area of ​​410m 2 / kg;

[0034] 5. Purchase desulfurization gypsum from power plants and pass it through a 2.36mm square hole sieve;

[0035] 6. The fineness modulus of machine-made sand is 2.9, which belongs to medium sand in zone II;

[0036] 7. Crushed stone is 4.95-19.0mm continuous graded limestone, with a crushing index of 11.8%;

[0037] 8. Early strength clinker-free concrete is prepared according to the following steps:

[0038] (1) The measured water content of the ammonia-soda mud is 53%, which is less than its liquid limit water content of 105%. The mass of the dry ammonia-soda mud is 74÷(1+53%)=48.4 kg;

[0039] (2) Each cubic meter of concrete requires an additional amount of water: 48.4 × (105% - 53%) = 25.2 kg;

[0040] (3) The actual mixing water consumption per cubic meter of concrete is 150 + 25.2 = 175.2 kg;

[0041] (4) Feed crushed stone, machine-made sand, ammonia-alkali white mud particles, slag powder, steel slag powder and desulfurized gypsum into a concrete mixer in sequence according to the mix ratio in Table 1 and stir for 30 seconds;

[0042] (5) Add 100 kg of mixing water into the mixer and stir for 30 seconds;

[0043] (6) Finally, 6.3 kg of polycarboxylate water reducer and the remaining 75.2 kg of mixing water were added to the mixer and stirred for 60 seconds to obtain an early strength clinker-free concrete mixture with a tested slump of 160 mm;

[0044] (7) The concrete mixture is placed into a 150 mm × 150 mm × 150 mm mold, compacted on a concrete compaction table, and covered with a plastic film;

[0045] (8) Place the mold filled with concrete in a curing room at 20±2℃ and relative humidity ≥95%, cure for 24 hours, remove from the mold, and continue to place it in the curing room for curing to the designed age, which is the early-strength clinker-free concrete.

[0046] 9. The compressive strength of the concrete at 1d is 8.0MPa, at 7d is 31.1MPa, and at 28d is 43.6MPa.

[0047] The difference from Example 1 is that this comparative example does not add ammonia-soda white mud, and other raw materials are the same.

[0048] 1. Use slag powder, steel slag powder, desulfurized gypsum, fine aggregate, coarse aggregate, polycarboxylic acid water reducer and water to prepare clinker-free concrete. The specific mix ratio is shown in Table 2.

[0049] Table 2 Concrete mix ratio (kg / m 3 )

[0050]

[0051] 2. Clinker-free concrete is prepared according to the following steps:

[0052] (1) Feed crushed stone, machine-made sand, slag powder, steel slag powder and desulfurized gypsum into a concrete mixer in sequence according to the mix ratio in Table 2 and mix for 30 seconds;

[0053] (2) Add 100 kg of mixing water into the mixer and stir for 30 seconds;

[0054] (3) Finally, 5.6 kg of polycarboxylate water reducer and the remaining 50 kg of mixing water were added to the mixer and stirred for 60 seconds to obtain a clinker-free concrete mixture with a slump of 150 mm.

[0055] (4) The concrete mixture is placed into a 150 mm × 150 mm × 150 mm mold, compacted on a concrete compaction table, and covered with a plastic film;

[0056] (5) The mold filled with concrete is placed in a curing room at 20±2℃ and relative humidity ≥95%. If it is not completely hardened after 24 hours of curing, it cannot be demoulded. If it can be demoulded after 48 hours of curing and continues to be placed in the curing room for curing to the designed age, it is clinker-free concrete.

[0057] 3. The concrete has no strength at 1 day; the compressive strength at 7 days is 19.5 MPa; the compressive strength at 28 days is 41.3 MPa. Example 2:

[0058] 1. Prepare early-strength clinker-free concrete with ammonia-alkali white mud, slag powder, steel slag powder, desulfurized gypsum, fine aggregate, coarse aggregate, polycarboxylic acid water reducer and water. The specific mix proportion is shown in Table 3.

[0059] Table 3 Concrete mix ratio (kg / m 3 )

[0060]

[0061] 2. The water content of ammonia-soda mud is 125%, and the liquid limit water content is 105%. The ammonia-soda mud is crushed into particles less than 2 mm by a crusher;

[0062] 3. Purchased steel slag powder, with a specific surface area of ​​360m 2 / kg;

[0063] 4. Purchase S95 grade granulated blast furnace slag powder, with a specific surface area of ​​410m 2 / kg;

[0064] 5. Purchase desulfurization gypsum from power plants and pass it through a 2.36mm square hole sieve;

[0065] 6. The fineness modulus of machine-made sand is 2.9, which belongs to medium sand in zone II;

[0066] 7. Crushed stone is 4.95-19.0mm continuous graded limestone, with a crushing index of 11.8%;

[0067] 8. Early strength clinker-free concrete is prepared according to the following steps:

[0068] (1) The measured water content of the ammonia-soda mud is 125%, which is greater than its liquid limit water content of 105%. The mass of the dry ammonia-soda mud is 148÷(1+125%)=65.8 kg;

[0069] (2) The water content of each cubic meter of concrete should be deducted by 65.8 × (125% - 105%) = 13.2 kg;

[0070] (3) The actual mixing water consumption per cubic meter of concrete is 160-13.2=146.8 kg;

[0071] (4) Feed crushed stone, machine-made sand, ammonia-alkali white mud particles, slag powder, steel slag powder and desulfurized gypsum into a concrete mixer in sequence according to the mix ratio in Table 3 and stir for 30 seconds;

[0072] (5) Add 100 kg of mixing water into the mixer and stir for 30 seconds;

[0073] (5) Finally, 6.0 kg of polycarboxylate water reducer and the remaining 46.8 kg of mixing water were added to the mixer and stirred for 60 seconds to obtain an early strength clinker-free concrete mixture with a tested slump of 170 mm;

[0074] (6) The concrete mixture is placed into a 150 mm × 150 mm × 150 mm mold, compacted on a concrete compaction table, and covered with a plastic film;

[0075] (7) Place the mold filled with concrete in a curing room at 20±2℃ and relative humidity ≥95%, cure for 24 hours, remove from the mold, and continue to place it in the curing room for curing to the designed age, which is the early-strength clinker-free concrete.

[0076] 9. The compressive strength of the concrete is 7.3MPa at 1d, 26.0MPa at 7d, and 37.3MPa at 28d.

[0077] Embodiment three:

[0078] 1. Prepare early-strength clinker-free concrete with ammonia-alkali white mud slurry, slag powder, steel slag powder, desulfurized gypsum, fine aggregate, coarse aggregate, polycarboxylic acid water reducer and water. The specific mix proportion is shown in Table 4.

[0079] Table 4 Concrete mix ratio (kg / m 3 )

[0080]

[0081] 2. The water content of ammonia-alkali white mud slurry is 145%, and the liquid limit water content is 105%;

[0082] 3. Purchased steel slag powder, with a specific surface area of ​​360m 2 / kg;

[0083] 4. Purchase S95 grade granulated blast furnace slag powder, with a specific surface area of ​​410m 2 / kg;

[0084] 5. Purchase desulfurization gypsum from power plants and pass it through a 2.36mm square hole sieve;

[0085] 6. The fineness modulus of machine-made sand is 2.9, which belongs to medium sand in zone II;

[0086] 7. Crushed stone is 4.95-19.0mm continuous graded limestone, with a crushing index of 11.8%;

[0087] 8. Early strength clinker-free concrete is prepared according to the following steps:

[0088] (1) The water content of the ammonia-soda white mud slurry was 145%, which was greater than its liquid limit water content of 105%. The mass of the dry ammonia-soda white mud was 170÷(1+145%)=69.4 kg;

[0089] (2) Each cubic meter of concrete needs to deduct 69.4 × (145% - 105%) = 27.8 kg of water;

[0090] (3) The actual mixing water consumption per cubic meter of concrete is 162-27.8=134.2 kg;

[0091] (4) Feed crushed stone, machine-made sand, ammonia-alkali white mud slurry, slag powder, steel slag powder and desulfurized gypsum into a concrete mixer in sequence according to the mix ratio in Table 4 and stir for 30 seconds;

[0092] (5) Add 100 kg of mixing water into the mixer and stir for 30 seconds;

[0093] (6) Finally, 7.7 kg of polycarboxylate water reducer and the remaining 34.2 kg of mixing water were added to the mixer and stirred for 60 seconds to obtain an early strength clinker-free concrete mixture with a tested slump of 170 mm;

[0094] (7) The concrete mixture is placed into a 150 mm × 150 mm × 150 mm mold, compacted on a concrete compaction table, and covered with a plastic film;

[0095] (8) Place the mold filled with concrete in a curing room at 20±2℃ and relative humidity ≥95%, cure for 24 hours, remove from the mold, and continue to place it in the curing room for curing to the designed age, which is the early-strength clinker-free concrete.

[0096] 9. The compressive strength of the concrete is 7.9MPa at 1d, 26.9MPa at 7d, and 39.8MPa at 28d.

[0097] Embodiment 4:

[0098] 1. Prepare early-strength clinker-free concrete with ammonia-alkali white mud, slag powder, steel slag powder, desulfurized gypsum, fine aggregate, coarse aggregate, polycarboxylic acid water reducer and water. The specific mix proportions are shown in Table 5.

[0099] Table 5 Concrete mix ratio (kg / m 3 )

[0100]

[0101] 2. The water content of ammonia-soda mud is 53%, and the liquid limit water content is 105%. The ammonia-soda mud is crushed into particles less than 2 mm by a crusher;

[0102] 3. Purchased steel slag powder, with a specific surface area of ​​360m 2 / kg;

[0103] 4. Purchase S95 grade granulated blast furnace slag powder, with a specific surface area of ​​410m 2 / kg;

[0104] 5. Purchase desulfurization gypsum from power plants and pass it through a 2.36mm square hole sieve;

[0105] 6. The fineness modulus of machine-made sand is 2.9, which belongs to medium sand in zone II;

[0106] 7. Crushed stone is 4.95-19.0mm continuous graded limestone, with a crushing index of 11.8%;

[0107] 8. Early strength clinker-free concrete is prepared according to the following steps:

[0108] (1) The measured water content of ammonia-alkali white mud is 53%, which is less than its liquid limit water content of 105%. Each cubic meter of concrete needs to be supplemented with additional water of 220÷(1+53%)×(105%-53%)=74.8 kg;

[0109] (2) The actual mixing water consumption per cubic meter of concrete is 154 + 74.8 = 228.8 kg;

[0110] (3) Feed crushed stone, machine-made sand, ammonia-alkali white mud particles, slag powder, steel slag powder and desulfurized gypsum into a concrete mixer in sequence according to the mix ratio in Table 5 and stir for 30 seconds;

[0111] (4) Add 150 kg of mixing water into the mixer and stir for 60 seconds;

[0112] (5) Finally, 10.5 kg of polycarboxylate water reducer and the remaining 78.8 kg of mixing water were added to the mixer and stirred for 60 seconds to obtain an early strength clinker-free concrete mixture with a tested slump of 180 mm;

[0113] (6) The concrete mixture is placed into a 150 mm × 150 mm × 150 mm mold, compacted on a concrete compaction table, and covered with a plastic film;

[0114] (7) Place the mold filled with concrete in a curing room at 20±2℃ and relative humidity ≥95%, cure for 24 hours, remove from the mold, and continue to place it in the curing room for curing to the designed age, which is the early-strength clinker-free concrete.

[0115] 9. The compressive strength of the concrete is 8.6MPa at 1d, 31.7MPa at 7d, and 47.5MPa at 28d.

[0116] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An early-strength clinker-free concrete prepared by using ammonia-alkali white mud, characterized in that: It includes the following components: calculated by mass: 65-235 parts of ammonia-alkali white mud, 140-245 parts of slag powder, 35-105 parts of steel slag powder, 30-60 parts of industrial by-product gypsum, 770-895 parts of fine aggregate, 1040-1070 parts of coarse aggregate, 5-9 parts of polycarboxylic acid water reducer and 120-166 parts of mixing water.

2. The early-strength clinker-free concrete prepared by ammonia-soda white mud according to claim 1, characterized in that: The compressive strength of the concrete after standard curing for one day after molding is ≥6.0MPa, the compressive strength after seven days is ≥20.0MPa, and the compressive strength after twenty-eight days is ≥35.0MPa.

3. The early-strength clinker-free concrete prepared by ammonia-alkali white mud according to claim 1, characterized in that: The ammonia-soda mud is obtained by mechanically crushing the wet-base ammonia-soda mud after filter pressing into particles of less than 2 mm; or the wet-base ammonia-soda mud after filter pressing is mechanically crushed and stirred into slurry with water, and the water content of the slurry is controlled to be ≥140%; the slag powder is S95 grade granulated blast furnace slag powder; the steel slag powder is steel slag powder after crushing, magnetic separation and grinding, with a specific surface area of ​​≥350m 2 / kg; the particle size of the coarse aggregate is 4.75-26.5mm, and the crushing index is ≤20%.

4. A method for preparing an early-strength clinker-free concrete prepared by using ammonia-alkali white mud, for preparing an early-strength clinker-free concrete prepared by using ammonia-alkali white mud as claimed in claims 1-3, characterized in that: The following steps are involved: A When using wet-base ammonia-alkali white mud particles crushed to less than 2 mm to prepare concrete, first take a sample of the ammonia-alkali white mud particles and dry them at 65°C to constant weight, and then test the moisture content to be a% and the liquid limit moisture content to be b%, and then adjust the water content; B. Feed coarse aggregate, fine aggregate, ammonia-alkali white mud, slag powder, steel slag powder and industrial by-product gypsum into a concrete mixer in the following proportions by weight: 1040-1070 parts of coarse aggregate, 770-895 parts of fine aggregate, 65-235 parts of ammonia-alkali white mud, 140-245 parts of slag powder, 35-105 parts of steel slag powder and 30-60 parts of industrial by-product gypsum, and stir for 30-60 seconds; C. first adding 50% to 80% of the total amount of the 120 to 166 parts of the mixing water into the mixer and stirring for 30 to 60 seconds; then adding 5 to 9 parts of the polycarboxylate water reducer together with the remaining mixing water into the mixer and stirring for 60 to 120 seconds to obtain a concrete mixture; D. The concrete mixture is vibrated into shape, placed in a curing room at 20±2° C. and relative humidity ≥95%, covered with a plastic film for moisture retention and curing for 24 hours, and then demolded to obtain an early-strength clinker-free concrete.

5. The early-strength clinker-free concrete prepared by using ammonia-soda white mud according to claim 4, characterized in that: The method for adjusting the water consumption comprises: when the water content of the ammonia-alkali white mud is measured to be a%<b%, it is necessary to add water on the basis of the water consumption, and the amount of added water is the mass of the dry ammonia-alkali white mud m·(b%-a%); When the moisture content of ammonia-alkali white mud is measured to be a%>b%, the actual mixing water consumption of concrete needs to deduct part of the water from the water consumption, and the amount of water deducted is the mass of dry ammonia-alkali white mud m·(a%-b%); When ammonia-alkali mud slurry is used to prepare concrete, the moisture content of the ammonia-alkali mud slurry is measured to be c%. Since c% ≥ 140%, it is higher than the liquid limit moisture content b% of the ammonia-alkali mud. At this time, the actual mixing water consumption of the concrete needs to deduct part of the water from the water consumption, and the deducted water amount is the dry basis ammonia-alkali mud mass m·(c%-b%).

Citation Information

Patent Citations

  • C30-grade all-solid-waste concrete and preparation method thereof

    CN112125633A

  • Clinker-free cementing material containing high-content wet-discharged alkaline residues as well as preparation method and application of clinker-free cementing material

    CN115745434A